Determination of green, blue and yellow artificial food colorants and their abuse in herb-coloured green Easter beers on tap. Issue 7 (2nd July 2016) - Stachová, Ivana; Lhotská, Ivona; Solich, Petr; Šatínský, Dalibor
ABSTRACT: Beer is one of the most popular alcoholic beverages worldwide. For consumer acceptance, significant factors are its taste, flavour and colour. This study determines selected synthetic green, blue and yellow food colorants in popular Easter herb-coloured green beers on tap produced in breweries on Holy Thursday. The abuse of beer colouring with Tartrazine (E 102), Quinoline yellow (E 104), Sunset yellow (E 110), Patent blue (E 131), Indigo carmine (E 132), Brilliant blue FCF (E 133), Green S (E 142) and Fast green FCF (E 143) was assessed in 11 green beer samples purchased in local restaurants. HPLC was used for the separation and detection of artificial colorants with diode-array detection and a Chromolith Performance CN 100 × 4.6 mm column with guard pre-column Chromolith CN 5 × 4.6 mm. Separation was performed in gradient elution with mobile phase containing methanol–aqueous 2% ammonium acetate at pH 7.0. The study showed that eight beers (70%) marketed in the Czech Republic contained artificial colorants (Tartrazine and Brilliant blue FCF). The concentration of colorants found in analysed green herb-coloured beers ranged from 1.58 to 3.49 mg l – 1 for Tartrazine, 0.45–2.18 mg l – 1 for Brilliant blue, while Indigo carmine was detected only once at concentration 2.36 mg l – 1 . Only three beers showed no addition of the synthetic colorants. However, the levels of artificial colorants found in beers marketed in the Czech region were very low and did not show a serious risk for consumers' health. GRAPHICAL ABSTRACT: